Design, synthesis and evaluation of carbazole derivatives as potential antimicrobial agents. (1st January 2021) - Xue, Yi-Jie; Li, Ming-Yue; Jin, Xue-Jun; Zheng, Chang-Ji; Piao, Hu-Ri
Abstract: Five series of novel carbazole derivatives containing an aminoguanidine, dihydrotriazine, thiosemicarbazide, semicarbazide or isonicotinic moiety were designed, synthesised and evaluated for their antimicrobial activities. Most of the compounds exhibited potent inhibitory activities towards different bacterial strains (including one multidrug-resistant clinical isolate) and one fungal strain with minimum inhibitory concentrations (MICs) between 0.5 and 16 µg/ml. Compounds 8f and 9d showed the most potent inhibitory activities (MICs of 0.5–2 µg/ml). Furthermore, compounds 8b, 8d, 8f, 8k, 9b and 9e with antimicrobial activities were not cytotoxic to human gastric cancer cell lines (SGC-7901 and AGS) or a normal human liver cell line (L-02). Structure–activity relationship analyses and docking studies implicated the dihydrotriazine group in increasing the antimicrobial potency and reducing the toxicity of the carbazole compounds. In vitro enzyme activity assays suggested that compound 8f binding to dihydrofolate reductase might account for the antimicrobial effect.